2016
DOI: 10.14503/thij-15-5692
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Left Subclavian Artery, Complete Atrioventricular Block, and Tricuspid Atresia in a Neonate

Abstract: Isolated left subclavian artery is one of the rarer aortic arch anomalies. It has been associated with other congenital heart diseases, typically tetralogy of Fallot, double-outlet right ventricle, and atrial and ventricular septal defects. Its significant clinical implications include a left-to-right shunt from the vertebrobasilar system, which causes pulmonary overcirculation and subclavian steal. We present an unusual case of a premature infant who was diagnosed prenatally with congenital complete atriovent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In up to 60% of isolated left subclavian cases, there are co-existent congenital heart defects, mostly Conotruncul anomalies such as double outlet right ventricle and tetralogy of Fallot, atrial septal defects and ventricular septal defects (9). Not surprisingly, our patient has multiple ventricular septal defects, the largest of which was a Perimambranous VSD with 6 mm diameter.…”
Section: Discussionmentioning
confidence: 65%
“…In up to 60% of isolated left subclavian cases, there are co-existent congenital heart defects, mostly Conotruncul anomalies such as double outlet right ventricle and tetralogy of Fallot, atrial septal defects and ventricular septal defects (9). Not surprisingly, our patient has multiple ventricular septal defects, the largest of which was a Perimambranous VSD with 6 mm diameter.…”
Section: Discussionmentioning
confidence: 65%
“…Ablation of a smaller area within the cardiac neural crest, results in the definitive aorta (fourth arch artery) is on the right, other malformations include double outlet right ventricle, tetralogy of Fallot et al 4,5 . Therefore, the above embryonic mechanisms can explain that ILSA is always associated with RAA, and more than half of ILSA is also associated with cardiac abnormalities, the most common being TOF, 6,7 there are also case reports related to the single ventricle, DORV, transposition of the great arteries, type I and II of aortopulmonary window, 8 coarctation, tricuspid atresia, 9 pseudopulmonary artery sling, 10 and other intracardiac abnormalities. All the CHD fetuses in our study were right aortic arch, and the intracardiac malformations were DORV and TOF, which suggested that when RAA was combined with those intracardiac malformations, it is necessary to pay attention to whether there is ILSA.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only two cases of a concomitant ISA and congenital complete atrioventricular block have been reported. 17,18 These two malformations may be derived from the same genetic defect or may be regulated by the same pathway. However, the family refused further genetic testing of the child after pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%
“…An early diagnosis in such a case might avoid unnecessary surgery, such as a Blalock-Taussig operation. 17…”
Section: Discussionmentioning
confidence: 99%